Faith and reason in the mad subjectivity: Cormac McCarthy’s post-apocalyptic narrative The Road - Taghizadeh, Ali; Ghaderi, Ali (Penerbit Universiti Kebangsaan Malaysia, 2016)
Identified as the core of human subjectivity, madness and the shattered self are among the issues which Cormac McCarthy represents in his brilliant though terrifying narrative The Road. This study attempts to address the representation of subjectivity’s faith and reason in the face of physical and mental struggles in his novel. Moreover, the relation that subjectivity has to the Big Other will be analyzed under Žižekian paradigms. In the pre-Kantian era, the human subject was to struggle against an extremity of madness so as to redeem itself a state of reason. But since Kant proposed that the core of subject/ivity can be madness itself, the struggles represented in McCarthy’s novel have been examined as significant events that show this core of inconsistency and madness. To do so, the present study analyzes his text to show the inconsistency of the subject/ivity of his characters along with the role of reason/madness and their relations to faith in the narrative. Particularly, it would be fruitful to focus on the contribution of what Žižek calls the “Light of Reason” and its fluctuations/fragmentations. The point opposite to this Light would be the Dark of the world, a dire night in which that mad center of human subjectivity could emerge into the novel’s events. For this purpose, the paper will elaborate more thoroughly on Derrida’s and Žižek’s viewpoints regarding Enlightenment and subjectivity. Of the main consideration in McCarthy’s text is deciding about life and death and about the force that compels his protagonists to keep fighting for their survival.